Radiotherapy of patients with squamous cell carcinoma metastatic to cervical lymph nodes from unknown primary site - Pszon, Joanna; Skołyszewski, Jan; Pudełek, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2005)
The paper presents results of a retrospective analysis of 127 patients with squamous cell carcinoma metastatic to the cervical lymph nodes from an unknown primary site radically treated in the Center of Oncology in Kraków between 1971 and 2001. Sixty three patients received combined therapy (surgery with postoperative irradiation), while sixty four patients underwent radiotherapy alone. Thirty four patients with N3, poorly differentiated carcinomas received induction chemotherapy CDDP + 5 FU. Forty one patients with poorly differentiated carcinomas received radiotherapy for both sides of the neck and all potential primary sites in the pharynx. Ipsilateral neck irradiation was delivered to 84 patients, 2 patients had both sides of the neck treated. One hundred and fifteen patients were treated with megavoltage external beam radiation with a total dose of 5850 cGy (on average), 12 patients were treated with fast neutrons with a total dose of 1274 cGy n,gamma (on average). The 5-year disease-free survival rate was 38.3%, while 10-year rate was 35.0%. The 5-year local control was positively correlated with tumor stage, histological grade, and irradiation of the whole pharynx. In thirteen patients local recurrence developed, and 35 patients did not have a complete response of the neck metastases. Twenty four patients developed distant metastases. The primary tumor site was later discovered in 16 patients’ head and neck organs, and only 3 of these patients were irradiated for bilateral neck and potential primary tumor sites. The treatment was well tolerated. Conclusions: our results suggest that the prognosis for the patients with squamous-cell cancer metastases in the cervical lymph nodes from an unknown primary site is rather poor. Patients with advanced stages of disease face a worse outcome. The prognosis improves when a large field prophylactic mucosal radiation therapy is applied.